Blood Sugar Levels With Neutrophil-Lymphocyte Ratio As a Marker of Diabetes Mellitus In Elderly - da Silva, Theodora E; Christine, Ika; Djaputra, Edith M (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Diabetes mellitus is a chronic metabolic disease, characterized by high blood sugar levels due to abnormal insulin secretion by the pancreas, insulin action, or both. Based on the Basic Health Research results in 2018, the elderly group dominates patients with diabetes mellitus. The diagnosis of diabetes mellitus requires an expensive examination that is not available in all laboratories, especially primary care facilities. Some research suggested that the neutrophil-lymphocyte ratio can be an alternative marker for establishing a diagnosis of diabetes mellitus. Purpose: To determine the correlation between blood sugar levels and lymphocyte ratio as a marker of diabetes mellitus in the elderly. Method: This study was an observational analytic study with a cross-sectional approach. Data was collected by conducting interviews, physical examinations, and laboratory examinations. Hypothesis testing in this study used the Spearman correlation test. Results: A total of 53 respondents were included in this study, with a proportion of 32 female subjects (60.4%). The mean age of respondents was 76.0 Â± 7.29 years. An insignificant correlation was obtained between fasting blood sugar levels and the ratio of neutrophil lymphocytes in the elderly (p = 0.161; r = 0.195). An insignificant correlation was found between blood glucose levels after two hours of postprandial with the neutrophil-lymphocyte ratio in the elderly (p = 0.595; r = 0.075). HbA1c level and the lymphocyte ratio in the elderly also showed a non-significant correlation (p = 0.873; r = -0.023) Conclusion: There is no significant correlation between blood sugar level and neutrophillymphocyte ratio as a marker of diabetes mellitus in the elderly.